COMPLEXO TENÍASE-CISTICERCOSE: UMA BREVE ABORDAGEM SOBRE A DOENÇA - da Silva, Leciane Rodrigues; Rutcoski, Vitória Modelski; Bavaresco, Kelly Cristina; Alves, Bruna Farias; Daneluz, Marina Oliveira; Schneider, Marla; Wurfel, Simone de Fátima Rauber (Anais de Medicina Veterinária; v. 2 n. 1 (2022): 2022/2, 2022)
.